An examination of cultural inclusion and Māori culture in New Zealand rugby : the impact on well-being : a thesis presented in partial fulfilment of the requirement for the degree of Doctor of Philosophy in Health (Sport & Exercise) at Massey University, Palmerston North, New Zealand - Hapeta, Jeremy William (Massey University, 2018)
This thesis presents four separate, yet related, studies. The purpose, as the title indicates, was to interrogate the inclusion of ‘culture’ (specifically in terms of ethnicity) within New Zealand Rugby environments and settings. Related to this primary objective, I also wanted to understand the impact of Māori knowledge practices on the well-being of players, coaches, other participants and communities. Each of the four studies aims to address these broad research objectives. A Kaupapa Māori approach guided the philosophical, theoretical and methodological perspectives utilised in each of the interrelated studies. Study 1 is a culturally progressive, Kaupapa Māori, review that synthesises the extant literature from 2008 to 2017of ethnicity and inclusion in sport globally, and Māori and rugby in New Zealand. The results showed that the main Māori symbol used in rugby was the haka. Thus, Study 2 examines whether the haka ‘Ka Mate’ is a commodity to trade or a taonga to treasure by analysing marketing campaigns related to sporting events. The pukengā (experts) interviewed would prefer it be treated as a taonga (treasure), not a commodity to maintain the well-being of this taonga and the communities who treasure it. The third study interrogates cultural identity and leadership practices from a Māori perspective by examining how indigenous storytelling impacted on well-being in a NZ provincial rugby team. The case study results demonstrated that a Māori motto (whakataukī), motif (maunga), mascots and a ‘maunga of success’ model were all used by the team (players and coaches/support staff) to enhance their individual and collective well-being, both on and off the field. The fourth study presents two other case studies that explore sport for social change inititiatives involving Māori and Pasifika rangatahi (youth) and rugby in New Zealand. Results showed that rugby and cultural identity can be used effectively as a waka (vehicle) to promote social and cultural change for youth. The concluding chapter discusses the outcomes of the overall research objectives where the studies’ limitations and strengths are also presented. Finally, implications for future research directions and recommendations are made.
Keywords: Rugby Union football; Social aspects; New Zealand; Maori (New Zealand people); Sports; Social life and customs; Ethnic identity; Well-being; New Zealand; Whutupōro; Māoritanga; Tuakiri; Ora; Māori Doctoral Thesis